Life which reflects the epoch (to Prof. D.P. Chukhriyenko centennial) - Ya. S. Bereznitsky; O. B. Kutovy; I. V. Lyulko; O. I. Reshetova; E. F. Samarets (Medičnì Perspektivi)
Life which reflects the epoch (to Prof. D.P. Chukhriyenko centennial)